Strategi Komunikasi Pandawara Group pada Kampanye #OneDayOneTrashBag untuk Edukasi Lingkungan melalui Media Sosial - Rachel Archita Salwa; M. Fikri Akbar; Nada Arina Romli (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
The issue of waste and the low level of public awareness regarding environmental cleanliness have become challenges that require effective communication strategies to encourage behavioral change. This study aims to identify the communication strategies used by Pandawara Group in the #OneDayOneTrashBag campaign to increase public awareness of the importance of environmental preservation through social media. This study employs a qualitative approach using a narrative method. Data collection was conducted through in-depth interviews, participatory observation, and documentation of the #OneDayOneTrashBag campaign activities. Data analysis was carried out through the stages of transcription, data selection, classification, and the construction of research narratives. The findings show that Pandawara Group’s communication strategy is developed through simple and easily understood message planning, the use of before-and-after visual content, the utilization of social media as a space for education and participation, and the establishment of interaction with audiences. The strategy is reflected through the aspects of plan, ploy, pattern, position, and perspective, which build Pandawara Group’s identity as an action-based environmental campaign movement. This study demonstrates that consistent, visual, and participatory digital communication can serve as an effective approach to increasing awareness and encouraging public involvement in environmental issues.